Penerapan Metode Sab’ah Pada Pembelajaran Ashwat Bagi Penutur Bahasa Arab Dewasa Tingkat Pemula di LTQ. Azkiya Kab. Bandung Jawa Barat - Susiawati Susiawati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
This research aims to find out the effectiveness of learning model of Ashwat. This research employs qualitative approach with a class action research technique. Results of this research is an Arabic language learning product about contrastive sound to improve Arabic language sound mastery for beginner native. The writer also found significant improvement, before and after learning. The comparative result shows, before the learning process participants who get excellent: 0%, very good: 0%, good: 0%, fair: 30%, minus: 10%, bad: 60% and after the treatment (post-test) the result is, Excellent: 90%, very good: 10%, good: 0%, fair: 0%, minus: 0%, bad: 0%.